ESCRTs breach the nuclear border - Webster, Brant M (Nucleus, 2015)
The endosomal sorting complexes required for transport (ESCRT) are best known for their role in sorting ubiquitylated membrane proteins into endosomes. The most ancient component of the ESCRT machinery is ESCRT-III, which is capable of oligomerizing into a helical filament that drives the invagination and scission of membranes aided by the AAA ATPase, Vps4, in several additional subcellular contexts. Our recent study broadens the work of ESCRT-III by identifying its role in a quality control pathway at the nuclear envelope (NE) that ensures the normal biogenesis of nuclear pore complexes (NPCs). Here, we will elaborate on how we envision this mechanism to progress and incorporate ESCRT-III into an emerging model of nuclear pore formation. Moreover, we speculate there are additional roles for the ESCRT-III machinery at the NE that broadly function to ensure its integrity and the maintenance of the nuclear compartment.